(3GdOQ GdeWdhH aj SQ GdZGdH hGdeZdhHs - (3CHh GdeMGSf jhSa Hf bhQbeGS GdMeRGhj GdJOQhej GdMdHj, LeGd GdOjf , CejQ MGL,J (B807 (3g` s
(3ChdgG (B:s
(3hHYO deG QCjJ Cgd ReGefG jHMKhf Yf CSQGQ GdZGdH ef Gdedhc deG OgeJge GdeMf hZdHJge GdaJf s
(3BNQgG (B:s
(3hGYde Cf gPG ef CSQGQ Gddg GdcGefg ai GdZjH , dcd ef GdeJMGQHjf ef ZjQ Tc hdG QjH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B153 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HGSJGfHhd (B(2472) s
Keywords: (3GdMQha h GdChaGbs